A Study of Chinese College Students’ English Listening Strategies - Bei, Zhang; Xinguang, SHAO (Advances in Social Sciences Research Journal, 2017)
This study investigates how Chinese college students apply English Listening strategies with questionnaires. The findings show that Chinese college students don’t do well in applying many English listening strategies, especially the metacognitive strategy of making plans, the cognitive strategy of inference and the social strategy of cooperation. Most students need to improve themselves in applying listening strategies so as to enhance their listening abilities. In English listening teaching, teachers should try to integrate the training of listening strategies into the normal classroom English teaching.